Sustainable Mangrove Ecotourism Management Model: A Case Study of Berau Regency, East Kalimantan - Rosid, Tamam; Yuliani, Ma'rifah (Indonesian Tourism Journal, 2025)
Berau Regency in East Kalimantan possesses significant mangrove forest resources with high biodiversity and ecosystem value, yet their utilization for ecotourism has remained suboptimal, leading to limited economic benefits and insufficient community engagement in sustainable development. Recognizing this gap, the study was designed to analyze and propose a sustainable mangrove ecotourism management model that integrates economic, environmental, and social dimensions to ensure long-term viability. The research employed a mixed-methods approach combining qualitative techniques such as in-depth interviews, focus group discussions, surveys, and stakeholder analysis, with quantitative tools including financial feasibility analysis, SWOT analysis, and business canvas modeling. Data were collected from 30 key informants, 200 respondents, and extensive field observations, supported by secondary statistical and planning documents. The findings reveal that Berau Regency’s mangrove ecotourism has substantial development potential, with an estimated revenue of Rp 9.8 billion by the fifth year, a positive Net Present Value of Rp 8,650 million, an Internal Rate of Return of 18.5%, and a payback period of 4.2 years, confirming financial feasibility. Furthermore, the proposed collaborative governance model, involving local government, communities, private sector actors, and NGOs, is projected to increase community income by 66.7%, create 450 new jobs, and enhance ecosystem conservation through structured monitoring. The study concludes that sustainable mangrove ecotourism in Berau Regency can be effectively achieved through integrated multi-stakeholder collaboration, balanced financial mechanisms, and adaptive management strategies, thereby contributing directly to local welfare improvement, biodiversity protection, and the advancement of Sustainable Development Goals.